Being there: cultural presence in electronic commerce. (13th February 2009) - Pennington, Robert
In contemporary consumer culture, products and brands carry cultural value that defines consumers and their relationships to their environments. To be effective in consumer marketing, electronic commerce must communicate cultural value by creating cultural presence in virtual environments that approximates actual environments. Presence the sense of being in an environment depends on the range of sensory inputs, the detail of the sensory inputs and the ability to choose and modify the available inputs. The sense of being in a social and cultural environment depends on sensory inputs and interactivity that identifies a cultural context. Effective virtual environments require not only mechanical sensory input range, detail and interactivity, but also cultural sensory input range, detail and interactivity.